Preparation & Characterization of Microcrystalline Cellulose from Agriculture Waste. Issue 1 (December 2020) - Senusi, Nur Aiman; Mohd Shohaimi, Norshahidatul Akhmar; Halim, Ahmad Zamani Ab; Shukr, Nurasmat Mohd; Abdul Razab, Mohammad Khairul Azhar; Mohamed, Mazlan; Mohd Amin, Mohamad Asyraf; Mokhtar, Wan Nur Aini Wan; Ismardi, Abrar; Mohamed Noor, An'Amt Bin; Abdullah, Nor Hakimin
Abstract: In this work, microcrystalline cellulose was prepared from oil palm trunk by water treated fibre process and alkali bleaching. The prepared samples were characterized by using Fourier-transform infrared spectroscopy attenuated total reflectance (FTIR-ATR), Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD). FTIR-ATR spectra analysis indicates the presence of the hydroxyl group, alcohol, alkane/alkene and imine group. XRD patterns revealed the amorphous nature of the samples and the crystallinity index for extracted cellulose is 48.7 %. SEM images showed the fibrous structure of the microcrystalline cellulose with a size of 50 μm. This research proved that the synthesized microcrystalline cellulose could be potentially used as reinforcement in bio composite for better performance and ductility.